Fast-acting insulin aspart (Fiasp®) improves glycemic outcomes when used with MiniMedTM 670G hybrid closed-loop system in simulated trials compared to NovoLog®. (June 2021) - Grosman, Benyamin; Wu, Di; Parikh, Neha; Roy, Anirban; Voskanyan, Gayane; Kurtz, Natalie; Sturis, Jeppe; Cohen, Ohad; Ekelund, Magnus; Vigersky, Robert
Highlights: Faster insulin action is hypothesized to improve closed-loop system results with insulin dependent Diabetes. We studied using Medtronic MiniMed TM novel simulation environment the benefits of switching between NovoLog® to Fiasp® insulin (Novo Nordisk A/S, Bagsværd, Denmark) with the MiniMed TM 670G system (Medtronic, Northridge, CA, USA). The simulation studies were compared with clinical results. Abstract: Introduction: Medtronic has developed a virtual patient simulator for modeling and predicting insulin therapy outcomes for people with type 1 diabetes (T1D). An enhanced simulator was created to estimate outcomes when using the MiniMed TM 670G system with standard NovoLog® (EU: NovoRapid, US: NovoLog) versus Fiasp ® by using clinical data. Methods: Sixty-seven participants' PK profiles were generated per type of insulin (Total of 134 PK profiles). 7, 485 virtual patients' PK measurements was matched with one of the 67 NovoLog® PK Tmax values. These 7, 485 virtual patients were then simulated using the Medtronic MiniMed™ 670G algorithm following an in-silico protocol of 90 days: 14 days in open loop (Manual Mode) followed by 76 days in closed loop (Auto Mode). Simulation study was repeated with each NovoLog® PK profile being replaced by its corresponding Fiasp® PK profile in the same virtual patient. To validate our in-silico analysis, we compared the results of "actual" 19 "real life" patients from a clinical study Results: Simulated overall and postprandial glycemic outcomes improved in all age groups with Fiasp®. The percentage of time in the euglycemic range increased by about 2.2% with Fiasp®, in all age groups (p < 0.01). The percentage of time spent at <70 mg/dL was reduced by about 0.6% with insulin Fiasp® (p < 0.01) and the mean glucose was reduced by about 1.3 mg/dL (p < 0.01), excluding those age <7 years. The simulated mean postprandial SG was reduced by 5 mg/dL, a significant difference for all age groups. A clinical study results showed similar improvements with MiniMed TM 670G system when switching from NovoLog® to Fiasp®. Conclusions: The simulation studies indicate that using Fiasp® in place of NovoLog® with the MiniMed TM 670G system will significantly improve the time spent in the healthy, euglycemic range and reduce exposure to hyperglycemia and hypoglycemia in most patients.